Exploring The Potential Of Optimised Starch Particulates As Platform For Oral Delivery Of A Model Gastrolabile Drug Cefotaxime - Bukhari, Nadeem Irfan (2009)
Use of particulates is a prominent approach for engineering delivery systems to overcome gastrointestinal barriers. Penggunaan zarah adalah pendekatan utama untuk sistem penghantaran kejuruteraan bagi mengatasi rintangan-rintangan di gastrousus.